ANALYSIS INTELLECTUAL CAPITAL ON FINANCIAL PERFORMANCE AND SUSTAINABLE GROWTH OF COMPANY IN INDONESIA - Farsiana Andini; Ririen Setiati Riyanti (Departemen Manajemen Fakultas Ekonomi dan Bisnis Universitas Negeri Malang, 2025)
The objective of this study is to examine the impact of Intellectual Capital (IC) on financial performance and sustainable growth within consumer goods sector companies in Indonesia over the period from 2018 to 2022. The research employs a multiple regression analysis method to assess the relationship between IC variables—measured using the Value Added Intellectual Coefficient (VAIC)—and its components: Capital Employed Efficiency (CEE), Human Capital Efficiency (HCE), Structural Capital Efficiency (SCE), Innovative Capital Efficiency (RDE), and Relational Capital Efficiency (RCE), in relation to financial performance indicators such as Return on Assets (ROA), Return on Equity (ROE), Sales Growth (SG), and Sustainable Growth Rate (SGR). The results of the analysis indicate a relationship between IC and financial performance, where VAIC demonstrates a significant influence on ROA, ROE, SG, and Sustainable Growth Rate (SGR) in the companies. However, findings regarding the individual IC components (CEE, HCE, SCE, RDE, and RCE) reveal varying effects on financial performance (ROA, ROE, and SG) and SGR. The implications of this study emphasize the critical importance of effective management and development of Intellectual Capital for companies, particularly in enhancing financial performance and achieving sustainable growth.